PENGARUH LATIHAN VARIASI TERHADAP KEMAMPUAN SHOOTING BOLA BASKET PADA CLUB BASKET PUTRA LBC (LILY BASKET CLUB) PEKANBARU - Nurmasita, Radha; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem with this research it still a lack of mastering techniques under the basket shoot. in addition, athletes also often incorrectly take into the angle of the ball on the basketball throw so the ball more often just pass over the opponent basketball ring. The study research to determine whether there is effect of variation training on basketball shooting ability at Basketball Club Putra LBC (Lily Basket Club) Pekanbaru. Type of research used is experiment and using one preetest-posttest disign. Population is research in Men’s Basketball Club LBC (Lily Basketball Club) Pekanbaru is the entire populations of 10 people. While the sample technique used is total sampling (saturated sample) where all the population is sampled. The sample in this study amounted to 10 people of Men’s Basketball Club LBC(Lily Basketball Club). The instruments use in this research is to test basketball shooting for 60 seconds. After that, the data is processed with statistics, normality test with lilifors test at significance level ɑ (0.05). The hypothesis is the effect of variation exercises on the shooting ability of the men's basketball. Based on the analysis of statistical data, there are an average pree-test 19,90 and an average post-test 30,30, then the data is normal with an increase of 10.40 . Based on t test analysis produces t hitung = 8.918 > t tabel = 1.833. Meaning t hitung > t tabel. Thus, there effect of exercise variation of Club Basketball Putra LBC (Lily Basket Club) Pekanbaru on basketball ability shooting of LBC Basketball Club (Lily Basket Club) Pekanbaru.Keywords : Variation Training, Shooting Ability, Basketball